2017
DOI: 10.1016/j.eswa.2017.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Developing an early-warning system for air quality prediction and assessment of cities in China

Abstract: Developing an early-warning system for air quality prediction and assessment of cities in China, Expert Systems With Applications (2017), Highlights  An early-warning system is developed for air quality.  Pollutant emission characteristics are analyzed using distribution functions.  Dynamic forecast intervals are constructed for addressing the uncertainty.  Air quality is evaluated by integrating fuzzy set theory and AHP.  The results show that the developed early-system is effective and reliable. Dear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…The forecasting of air quality became popular, many methods have been purposed for forecasting air quality such as hidden Markov model [15], first-order and one-variable grey model [16], developed support vector machine [17], fuzzy time series model [18][19] [25], Solar Radiation [26], and Fuzzy-AHP [27].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The forecasting of air quality became popular, many methods have been purposed for forecasting air quality such as hidden Markov model [15], first-order and one-variable grey model [16], developed support vector machine [17], fuzzy time series model [18][19] [25], Solar Radiation [26], and Fuzzy-AHP [27].…”
Section: Related Workmentioning
confidence: 99%
“…Compared with forecasting, determination of air pollution has recently become an important issue due to https://doi.org/10.1051/e3sconf/2018730 , 0 (2018) E3S Web of Conferences 73 ICENIS 2018 50 50 26 26 its significance, and several new methodologies have been developed for the determination of air quality, such as Fuzzy-AHP [27], artificial neural networks [28], and real-time measurement [29]. Based on the literature on the determination of air quality mentioned above, real-time measurement became an important issue since air pollution parameters difficult detected by a human body.…”
Section: Related Workmentioning
confidence: 99%
“…Consequently, these proxies are unable to evaluate and assess the estimation uncertainty. For instance, if there is a sudden increase of pollutant concentration estimation, it is not possible to assess its confidence interval [26,27]. Therefore, additional measurements and validation may be required to confirm the estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used machine learning algorithms include multiple linear regression (MLR), random forest (RF) [23], support vector regression (SVR) [24], artificial neural networks (ANN) [25], and so forth. Previous studies have found that machine learning methods achieve excellent performance due to the nonlinear relationships within data, meaning that these methods are better suited to parameter statistic models and need less training time than dispersion models [26][27][28]. Deep learning algorithms, as a relative newcomer, have obtained outstanding prediction or detection performances in various application domains such as speech recognition, natural language processing, and computer vision [29].…”
Section: Introductionmentioning
confidence: 99%